KONSEP IQTHA’ PEMBERIAN TANAH KEPADA MASYARAKAT DALAM PEMIKIRAN EKONOMI AL-MAWARDI (STUDI KITAB AL-AHKAM ALSULTANIYYAH) - Mujahidin Mujahidin (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2017)
Land is part of the earth as the ultimate gift of God which is governed by the State and used for the greatest prosperity of the people as mandated by the 1945 Constitution of the Republic of Indonesia. This research will raise the concept of iqtha 'in Islamic government through Al-Mawardi's thought in his book al-ahkam al-sultaniyyah by comparing it with the Indonesian land management sistem. The purpose of this study was to find out the concept of iqta 'in Islamic governance through the thinking of AlMawardi in his book al-ahkam al-sultaniyyah. Al-Mawardi in his book that iqtha is the giving of land to the community by the head of state, but the land that can be given is land which is his authority, namely no-man's land and abandoned land and no one manages it in the Indonesian context. bertuan but wild land (waste land) or referred to as vacant land and it is all controlled by the State except those cultivated by the community or residents with rights originating from the right to open land.